Counseling lifestyle medicine in oncology: a qualitative analysis of interprofessional patient-nurse-physician interactions - Klafke, Nadja; Bossert, Jasmin; Boltenhagen, Ursula; Froehlich, Daniela; Mahler, Cornelia; Joos, Stefanie; Wensing, Michel (Patient education and counseling, 2024)
Objectives - Counseling plays a key role in promoting health behaviors, providing evidence-based information, and supporting patients with cancer during and after treatment. This study aimed to evaluate an interprofessional counseling service on Complementary and Integrative Health (CIH) for patients being treated at Comprehensive Cancer Centers (CCCs) in Southern Germany. - Methods - Patients participating in the CCC-Integrativ study received three CIH counseling sessions within three months in addition to their conventional cancer treatment. Medical and nursing staff participated in a study-specific blended learning training program before conducting the counseling. As part of the process evaluation, 30 audio-recorded counseling sessions were transcribed verbatim and analyzed by conducting a content analysis using MAXQDA 2020. - Results - Throughout the counseling, patients were conceded to address various health issues, which mainly revolved around symptom management interlaced with the areas of nutrition, exercise, and relaxation. The interprofessional teams conducted the counseling in a structured and patient-oriented manner. They worked together to motivate the patients to apply procedures from the CIH field independently, even if patients sometimes experienced difficulties in implementation. - Conclusions - Interprofessional collaboration improved healthcare quality, as patients received comprehensive and evidence-based advice on their supportive needs and lifestyle issues. Both professions could equally contribute their areas of knowledge and expertise and apply them to the benefit of the patients. - Practice implications - Providing an integrative counseling service and adequate training on interpersonal communication and CIH for healthcare professionals will improve patient-centered care.
Online verfügbar 16 June 2024, Version des Artikels 20 June 2024
Gesehen am 02.06.2025